Ability of various proteins to form thermostable gels with propylene glycol alginate - Mohamed, Suhaila; Stainsby, George (Elsevier, 1984)
Propylene glycol alginate forms gels with proteins in alkaline conditions (pH 9.3 to 10.5). The ability of gelatin, casein, soya isolate, whey protein concentrate, egg albumin and bovine serum albumin to form ‘protein-alginate’ gels was investigated. Conditions were varied so as to alter the structures of the protein and observe the effect on gel formation. These conditions include changing pH, heat, the action of nitrous acid, SDS, mercaptoethanol, hydrogen bond breakers and changing concentration of the protein. The extent of gel formation was indicated by its rigidity modulus. The tertiary structure of the protein appears to be a very important factor in the gel formation. The gels are readily brought down to pH values more suitable for foods, and are stable to heating at 95°C and to freeze-thawing.